Synthesis of Nickel-Encapsulated Carbon Nanocapsules and Cup-Stacked-Type Carbon Nanotubes via Nickel-Doped Fullerene Nanowhiskers - Tokushi Kizuka; Kun'ichi Miyazawa; Akira Akagawa (Journal of Nanotechnology)
Nickel- (Ni) doped C60 nanowhiskers (NWs) were synthesized by a liquid-liquid interfacial precipitation method using a C60-saturated toluene solution and isopropanol with Ni nitrate hexahydrate Ni(NO3)2·6H2O. By varying the heating temperature of Ni-doped C60 NWs, two types of one-dimensional carbon nanostructures were produced. By heating the NWs at 973 and 1173 K, carbon nanocapsules (CNCs) that encapsulated Ni nanoparticles were produced. The Ni-encapsulated CNCs joined one dimensionally to form chain structures. Upon heating the NWs to 1373 K, cup-stacked-type carbon nanotubes were synthesized.